Public Relations or Humas: How do the public and practitioners perceive it? - Rachmat Kriyantono; Choiria Anggraini (Fakultas Ilmu Komunikasi UKWMS, 2020)
This study aims to describe the public and practitioner's perceptions of the public relations or Humas profession. Public relations plays a role in maintaining the credibility of the organization which is built from public perceptions. Apart from public relations, this profession is also called humas. However, based on Propechy's Self-Fulfilling Theory, it is possible to have different meanings by the public and practitioners related to these two terms. This study uses a constructivist approach (qualitative) and interview methods to collect data. The number of informants was 200 people in Malang City. The focus of this research is to find perceptions about what public relations or humas is, its functions, its relation to gender, and educational background. This research produces four propositions, namely public and practitioner perceptions of public relations and humas tends to be positive, public relations and humas are considered the same profession, men and women are perceived to be practitioners in this profession, and practitioners should come from the discipline of communication science and public relations. This research contributes to challenge the previous view that public relations is seen as an attempt to manipulate communication messages.